Bad form social mistakes and the nineteenth-century novel - Puckett, Kent.; Oxford eBooks (Oxford : Oxford University Press, 2008)
With significant new readings of a number of 19th-century works such as Eliot's 'Middlemarch', Flaubert's 'Madame Bovary', and James's 'The Princess Casamassima', Kent Puckett reveals how the novel achieves its coherence thanks to minor mistakes that novels both represent and make.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Flaubert, Gustave, -- 1821-1880 -- Knowledge -- Manners and customs; Eliot, George, -- 1819-1880 -- Knowledge -- Manners and customs; James, Henry, -- 1843-1916 -- Knowledge -- Manners and customs; Fiction -- 19th century -- History and criticism; Manners and customs in literature; English fiction -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 19th century; French fiction -- 19th century -- History and criticism; Literature and society -- France -- History -- 19th century; Electronic books